Empirical and theoretical considerations toward a model for caribou socioecology - Davis, James L.; Valkenburg, Patrick; Boertje, Rodney D. (Rangifer, 1986)
The Delta and Yanert caribou (Rangifer tarandus granti) herds apparently maintained discrete calving areas from 1979 through 1983 (as determined by radio telemetry studies), even though substantial intermixing occurred during other seasons. Also, the Delta herd apparently used a single traditional calving area from the 1950's through 1983, based on results of aerial surveys and 1979-83 telemetry studies. Calving distribution in 1984 changed dramatically; 5 of 25 radio-collared Delta herd cows ^3 years old and 5 of 24 radio-collared Delta herd cows <3 years old were located in the calving area of the Yanert herd, 72 km west-southwest of the traditional Delta herd calving area. Use of traditional, separate calving areas resumed for the two herds in 1985. One implication of these data is that the current definition of a caribou herd may not always apply. A second implication is that current models of caribou socioecology, based largely on the concepts of traditional use of calving grounds, herd identity/fidelity, and dispersal, inadequately predict or explain all empirical observations. An evolving model of optimal and dynamic use of space can help refine current models of caribou socioecology.